2003
DOI: 10.1046/j.1365-3148.2003.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Remuneration for blood donation and attitudes towards blood donation and receipt in Leeds

Abstract: In a survey of attitudes towards remuneration for blood donation in Leeds, the following questions were completed by 489 adults (N), of whom 89 were regular donors, 105 were lapsed donors and 295 had never donated: 'If you needed blood, would you be content if the donor had been paid: yes/no'. 'If I were paid enough I would be less/equally/more likely to donate blood '. The majority (67.7%) of potential recipients would be content if the donor had been paid. The prospect of remuneration made 16.4% of responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 16 publications
2
16
1
Order By: Relevance
“…A study from USA found financial motivation of donors to be most pronounced among Hispanics. [31] On the other hand a recent study from Leeds[32] found that the majority (67.7%) of potential recipients of blood do not object to donors been paid. Also, the prospect of remuneration made 16.4% of the respondents more likely to donate.…”
Section: Discussionmentioning
confidence: 99%
“…A study from USA found financial motivation of donors to be most pronounced among Hispanics. [31] On the other hand a recent study from Leeds[32] found that the majority (67.7%) of potential recipients of blood do not object to donors been paid. Also, the prospect of remuneration made 16.4% of the respondents more likely to donate.…”
Section: Discussionmentioning
confidence: 99%
“…Research from other areas indicates that a crowding-out effect due to payment might occur [41][42][43], but this cannot be readily transferred to blood donation. In studies asking for future blood donation behaviour, a crowdingout effect has not been shown [44][45]. A study specifically designed to examine crowding out in a real life donation situation has been conducted in Sweden by Mellström and Johannesson.…”
Section: Destruction Of Altruism/crowding Out?mentioning
confidence: 99%
“…An alternative explanation lies in the assumed altruism of donors (Boe & Ponder, 1981;Glynn et al, 2002;Jones et al, 2003;Titmuss, 1970 (National Blood Authority, 1998;Piliavin & Callero, 1991). In addition, claims for the role of altruism are poorly supported and open to alternative interpretation (Rapport & Maggs, 2002).…”
Section: Introductionmentioning
confidence: 99%